The Role of Schools in Multicultural Education, Development of Multicultural Education - Marhadi Efendi; Syafrianto Syafrianto; Mahyudin Ritonga; Julhadi Julhadi (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
Multicultural education is a strategic approach in responding to the reality of the diversity of the Indonesian nation consisting of various ethnicities, religions, races, and cultures. This study aims to analyze the role of schools in implementing multicultural education and its development strategies within the context of the Indonesian national education system. The method used is a literature study with a qualitative-descriptive approach, through the analysis of various literature, theoretical concepts, and educational policies relevant to multiculturalism and educational practices in schools. The results of the study indicate that schools have a central role as agents of socialization of the values of tolerance, equality, and respect for diversity through curriculum, learning, school culture, teacher training, and parental and community involvement. The development of multicultural education can be done through the integration of multicultural materials in subjects, the establishment of special subjects, planned institutional programs, and social movements that promote equality and justice. Furthermore, the application of Banks' five dimensions of multicultural education—namely, material integration, knowledge construction, prejudice reduction, equitable pedagogy, and empowerment of school culture—serves as an important framework for addressing various implementation challenges, such as teachers' limited understanding of students' cultures and persistent social prejudice. The conclusion of this study confirms that strengthening the role of schools in multicultural education is key to realizing an inclusive, tolerant, and civilized Indonesian society in the face of the dynamics of globalization and cultural plurality.